Functional outcome and the structural integrity of arthroscopic Bankart repair: a prospective trial. Issue 2 (April 2015) - Zhu, Mark; Young, Simon W; Pinto, Clinton; Poon, Peter C
Background: Recurrent anterior shoulder dislocations are common in young patients with Bankart lesions. Arthroscopic repair is an established treatment; however, recurrent instability occurs in up to 35% of patients. It is unclear whether recurrence is the result of a failure of the surgical repair to heal or a repeat injury. The aim of the present pilot study was to assess radiographic healing of Bankart lesions 6 months post surgical repair and identify any correlations between radiographic findings and subsequent recurrent dislocations. Methods: Eighteen patients underwent arthroscopic Bankart repair for recurrent instability. Magnetic resonance (MR) arthrograms were obtained both pre-operatively and 6 months postoperatively. Standard T1 and T2 views were obtained along with an abduction and external rotation (ABER) view. Patients were followed for a minimum of 4 years for the risk of recurrence, and functional outcomes were obtained, including the American Shoulder and Elbow Surgeons Subjective Shoulder Scale, Ontario Shoulder Instability Index, Oxford Shoulder Instability Score and 12-Item Short Form Health Survey. Scores were correlated with pre-operative and postoperative MR findings. Results: Six of 18 patients developed recurrent instability. We could not identify correlations between reconstructed labrum (labral bumper) position, failure at suture sites and ABER findings with recurrent instability or functional outcome. Paradoxically, there was a nonstatistically significant trend for patients with no clefts between the labrum and the glenoid at any points along the repair to have worse outcomes than patients with partial or complete clefts. Conclusions: In our pilot study, MR arthrogram was used to evaluate the labrum in detail 6 months postoperatively. Despite its proven ability to detect labral lesions, we were unable to demonstrate any features on postoperative MR arthrogram that predicted either functional outcome or recurrent instability. At 6 months post operation, functional recovery and the risk of recurrence may not depend on the anatomical appearance of the labrum alone.